1979
DOI: 10.1136/ard.38.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Juxta-articular adiposis dolorosa: what is it? Report of 2 cases.

Abstract: suMMARY Juxta-articular adiposis dolorosa may be defined as the localised accumulation of painful fat near joints, most commonly the knee. It exists as a separate entity that must be distinguished from other causes of knee pain. We present 2 patients with this condition and review the literature. Various approaches to therapy are discussed. A classification of painful fat near joints is proposed.Juxta-articular adiposis dolorosa (JAD)-does it exist? What is it? Literally it means painful fat near a joint. We b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…These cases are similar to lipedema in terms of the pattern of painful fat (less likely early on in the hands, feet, face, and forearms) and the latter case describes well the distinct "bracelet" of fat seen at the base of the leg above the foot that is classic in lipedema [112] . The published photographs of the columnar legs with the cuff of fat above the foot, or the mass of tender fat inferomedial to the knee, and the enlarged upper arms in DD are consistent with lipedema [112,183,184,224,225] .…”
Section: Physiology Of Ddmentioning
confidence: 86%
“…These cases are similar to lipedema in terms of the pattern of painful fat (less likely early on in the hands, feet, face, and forearms) and the latter case describes well the distinct "bracelet" of fat seen at the base of the leg above the foot that is classic in lipedema [112] . The published photographs of the columnar legs with the cuff of fat above the foot, or the mass of tender fat inferomedial to the knee, and the enlarged upper arms in DD are consistent with lipedema [112,183,184,224,225] .…”
Section: Physiology Of Ddmentioning
confidence: 86%
“…Kling reviewed 112 patients and suggested that juxta-articular Dercum’s disease could be a precursor to the diffuse generalised type of Dercum’s disease . Since then, three cases of juxta-articular Dercum’s disease in association with seropositive rheumatoid arthritis have been reported [44,45], and [Weinberger et al 45] have speculated on whether juxta-articular Dercum’s disease could actually be an extra-articular manifestation of rheumatoid arthritis. Furthermore, Kling has come up with the theory that adipose tissue deposits around the knees might interfere with the blood supply, by pressure on the joint, and result in the development of painful osteo-arthritis [43].…”
Section: Classificationmentioning
confidence: 99%
“…4 The lipomas typically display a periarticular presentation that differs from our patient. 7 The finding of neurogenic elements in histologic examination does not support the diagnosis of lipomas. Multifocal hemangiomas or venous malformations are exceedingly rare out outside of syndromes with associated vascular abnormalities such as Maffucci's or KlippelTrenaunay.…”
Section: Discussion and Treatmentmentioning
confidence: 93%